Green Accounting and Corporate Social Responsibility on Firm Value: A Study of the Consumer Cyclicals Sector - Trisma Listiani Dewi; Sandra Sukma Embuningtiyas (Universitas Serang Raya, 2026)
This study aims to provide empirical evidence on the effect of green accounting implementation and corporate social responsibility disclosure on firm value. The study population is cyclical consumer goods sector companies listed on the Indonesia Stock Exchange and Singapore Stock Exchange in the period 2020–2022. Using purposive sampling technique, 83 companies were obtained that met the criteria as samples. Secondary data were analyzed using multiple linear regression and hypothesis testing. This study uses green accounting and CSR as independent variables, firm value as the dependent variable, and firm size and profitability as control variables. The results of the study indicate that the implementation of green accounting and CSR disclosure have a positive effect on firm value. This finding emphasizes the importance of sustainable business practices that not only provide financial benefits but also contribute to the welfare of the environment and society. This study provides important insights to encourage corporate commitment to sustainability that is aligned with economic, ecological, and social goals. Keywords: Green Accounting, Corporate Social Responsibility, Firm Value, Firm Size, Profitability